The Dao of civilization : a letter to China - Mathews, Freya, 1949- (Anthem Press, 2023)
The book sets out a prospectus for a new form of civilization patterned at every level to serve and sustain the biosphere. It calls on China to lead the world towards this new era by re-crafting its own civilization in accordance with its indigenous tap-root: Dao.